Epistemic Curiosity Scale for Young Children: A Scale Adaptation to Turkish - Seda Saraç; Enisa Mede; Tuğba Abanoz (Psikoloji Çalışmaları)
Epistemic curiosity is the desire to seek and acquire new information that motivates knowledge and exploratory behavior. While epistemic curiosity can stimulate positive feelings of interest related to novelty-seeking behavior and the intrinsic joy of discoveries (I-Type), it can also diminish unpleasant and uncertain experiences, which are associated with the feeling of being deprived of information (D-Type). Given the growing interest in epistemic curiosity and its implications in education, specific assessment tools are needed to measure early indicators of Type-I and Type-D epistemic curiosity, particularly in local contexts. In this study, the reliability and validity of the Turkish version of the I-Type/D-Type Epistemic Curiosity Scale for Young Children were investigated. The 10-item I-Type/D-Type Epistemic Curiosity Scale for Young Children was developed by Piotrowski and colleagues (2014) to assess children’s epistemic curiosity based on parents’ observations. The participants of the study were 636 children (F = 302; M = 334). The ages of the children ranged from 48 to 83 months (M = 68.34; SD = 7.96). Data were obtained from the mothers. The scale’s factor structure was tested with Confirmatory Factor Analysis. The results showed that the Turkish version of the scale also has a similar two-factor (I-Type/Y-Type) structure to the original scale. Furthermore, for construct validity, zero-order correlations reported a significant positive relationship between self-regulation and I-Type and D-type epistemic curiosity, as hypothesized. Additionally, a partial correlation between curiosity type and self-regulation highlighted the divergence of two I-Type and D-Type epistemic curiosity. These findings indicated that the 10-item, two-factor I-Type/D-Type Epistemic Curiosity Scale for Young Children is reliable and valid for assessing young children’s curiosity through mothers’ ratings.